Acute Intrauterine Asphyxial Encephalopathy - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 1998)
A clinical-imaging syndrome of acute near-total intrauterine asphyxia is described in 11 term infants followed at Evanston Hospital, and Northwestern University Medical School, Chicago, IL.